Creative Content Production Challenge and Engagement Instability Analysis of Bu Erte’s Woven Bags on Tiktok - Laylia Putri Ramadhanie; Restin Meilina (AIBPM Publisher, 2025)
This research investigates the content strategy of traditional craft MSMEs (Micro, Small, and Medium Enterprises) in response to engagement instability on TikTok. The study's significance lies in its effort to fill the literature gap regarding the impact of algorithmic uncertainty on the creative decisions of micro-entrepreneurs. Its objective is to analyze the meaning and adaptation strategies employed by the owner of